P755 Safety, efficacy, and pharmacokinetics of vedolizumab in patients with simultaneous exposure to an anti-TNF. (16th January 2018) - Ben-Horin, S; Ungar, B; Kopylov, U; Lahat, A; Yavzori, M; Fudim, E; Picard, O; Peled, Y; Eliakim, R; Del Tedesco, E; Paul, S; Roblin, X
Abstract: Background: Combo-biologics may be the next therapeutic breakthrough in IBD. However, data on dual biologics' exposure are still scant. Methods: This was a retrospective case–control study in two medical centres of patients who started vedolizumab after recent cessation of adalimumab or infliximab (one and three months, respectively). Patients without measurable anti-TNF levels in blood at vedolizumab initiation were excluded. Efficacy, safety and pharmacokinetics of vedolizumab induction were compared at 1:2 ratio between co-exposed 'VDZ-aTNF' patients and control VDZ patients matched for IBD type (UC or CD). In a prospective separate cohort of patients starting infliximab, the impact of infliximab initiation on the percentage of circulating α4β7+ memory T cells was examined by staining with a fluorescent-conjugated vedolizumab and FACS analysis. Results: Seventy-five patients were included: 25 VDZ-aTNF and 50 VDZ patients. Adverse events were experienced by 9/25 VDZ-aTNF compared with 13/50 VDZ patients ( p = 0.4). Three events (headache and mycobacterium marinum infection in VDZ-aTNF patients and acute sarcoidosis in a VDZ patient) led to therapy cessation. Week 14 clinical remission was achieved in 10/25 (40%) of the VDZ-aTNF patients vs. 23/50 (46%) of the VDZ group (OR=0.8, 95% CI 0.3–2.1, p = 0.6). Clinical response was attained by 19/25 (76%) VDZ-aTNF patients compared with 39/50 (78%) VDZ patients (OR=0.9 95% CI 0.3–2.7, p = 0.8). Corticosteroid-free remission and corticosteroid-free response were experienced by 30% and 54%, respectively, of the entire cohort, and their rates were not different between the VDZ-aTNF and VDZ groups. Vedolizumab drug concentrations at week 2, 6 and 14 were not different among VDZ-aTNF compared with VDZ patients ( p > 0.5 for all comparisons). Multi-variable analysis showed independent association of some vedolizumab drug levels time-points with baseline albumin and weight, but not with co-exposure to infliximab/adalimumab. In prospectively followed patients starting infliximab ( n = 12), the percentage of α4β7+ memory T-cells slightly increased from week 0, through week 2 to week 14 of infliximab (26 ± 2.3%, 27.8 ± 2.9%, 29.5 ± 2.6%, respectively, p = 0.06) although the increase in absolute percentage was small. Conclusions: Vedolizumab/anti-TNF co-exposure did not generate new safety signals, nor did it affect vedolizumab efficacy or reduce its drug levels during induction therapy. These data argue against the need for a deliberate waiting-interval between anti-TNF cessation and subsequent vedolizumab initiation and may also be useful for the design of future combo-biologics treatment trials.